2022
DOI: 10.1093/mnrasl/slac009
|View full text |Cite
|
Sign up to set email alerts
|

The luminosity-dependent contribution from the broad-line region to the wavelength-dependent lags in Mrk 110

Abstract: We have measured the wavelength-dependent lags between the X-ray, UV and optical bands in the high accretion rate ($L/L_{\rm Edd}\approx 40{{\ \rm per\ cent}}$) Active Galactic Nucleus Mrk 110 during two intensive monitoring campaigns in February and September 2019. We divide the observations into three intervals with different X-ray luminosities. The first interval, already published in Vincentelli et al. (2021), has the lowest X-ray luminosity and did not exhibit the U-band excess positive lag, or the X-ray … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 51 publications
1
16
0
Order By: Relevance
“…The Night 2 data strongly depart from the expected lag-wavelength trend in that the zband lag is shorter than the i-band lag, although the dominant reverberation behavior apparent in the combined Night 1+2 data follows the τ ∝ λ 4/3 model closely. Very few AGN have high-cadence continuum reverberation mapping data spanning timescales long enough to search for temporal changes in lags (one example is Mrk 110, which has shown evidence for a time-varying BLR contribution; Vincentelli et al 2022). In light of this unusual behavior, it would be particularly useful to carry out monitoring of NGC 4395 over a longer time baseline, and over a broader range of wavelengths (ideally including X-ray and UV observations) to better explore temporal changes in lag behavior, and test whether variations in lag are correlated with any other observable properties.…”
Section: Discussionmentioning
confidence: 99%
“…The Night 2 data strongly depart from the expected lag-wavelength trend in that the zband lag is shorter than the i-band lag, although the dominant reverberation behavior apparent in the combined Night 1+2 data follows the τ ∝ λ 4/3 model closely. Very few AGN have high-cadence continuum reverberation mapping data spanning timescales long enough to search for temporal changes in lags (one example is Mrk 110, which has shown evidence for a time-varying BLR contribution; Vincentelli et al 2022). In light of this unusual behavior, it would be particularly useful to carry out monitoring of NGC 4395 over a longer time baseline, and over a broader range of wavelengths (ideally including X-ray and UV observations) to better explore temporal changes in lag behavior, and test whether variations in lag are correlated with any other observable properties.…”
Section: Discussionmentioning
confidence: 99%
“…The Night 2 data strongly depart from the expected lag-wavelength trend in that the z-band lag is shorter than the i-band lag, although the dominant reverberation behavior apparent in the combined Night 1+2 data follows the τ ∝ λ 4/3 model closely. Very few AGN have high-cadence continuum reverberation mapping data spanning timescales long enough to search for temporal changes in lags (one example is Mrk 110 which has shown evidence for a time-varying BLR contribution; Vincentelli et al 2022). In light of this unusual behavior, it would be particularly useful to carry out monitoring of NGC 4395 over a longer time baseline, and over a broader range of wavelengths (ideally including X-ray and UV observations) to better explore temporal changes in lag behavior, and test whether variations in lag are correlated with any other observable properties.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, Vincentelli et al (2022), together with Vincentelli et al (2021), observed an opposite trend in two intensive reverberation monitoring campaigns on Mrk 110. They divided two campaigns into three intervals based on X-ray luminosity, and found that the U-band lag excess is not observed in the lowest X-ray state but is seen in two subsequent intervals with higher X-ray luminosities, which indicates an opposite luminosity-dependent diffuse BLR lag in Mrk 110.…”
Section: Larger-than-expected Disk Sizementioning
confidence: 96%